Mocetinostat (MGCD0103): a review of an isotype-specific histone deacetylase inhibitor - Boumber, Yanis (Expert Opin Investig Drugs, 2011)
INTRODUCTION: HDAC inhibitors (HDACIs) have the potential to restore gene expression and display antitumor effects in vitro. As single agents, HDACIs have clinical activity in lymphoma. In myeloid leukemias, combinations of DNA methylation inhibitors and HDACIs are promising. Other combinations are being studied in solid tumors. AREAS COVERED: This article covers basic information and an update on preclinical and clinical experience with the oral isotype-selective HDACI MGCD0103 (mocetinostat) in hematological malignancies and solid tumors. It also examines data concerning MGCD0103 from recent conferences and articles through to November 2010, including new data regarding responses in lymphoma and toxicities. EXPERT OPINION: MGCD0103 is well-tolerated and exhibits favorable pharmacokinetic and pharmacodynamic profiles, demonstrating target inhibition and clinical responses. It induces cell death and autophagy, synergizes with proteasomal inhibitors and affects non-histone targets, such as microtubules. In 2008, new patient enrollment in trials was temporarily suspended due to potential cardiac complications. This restriction was lifted in 2009 as no correlation between MGCD0103 exposure and pericardial effusions was found. New patient enrollment in MGCD0103 clinical trials requires the exclusion of patients diagnosed with significant cardiac abnormalities prior to enrollment. Clinical and pharmacodynamic data support a three-times-weekly administration at a 90 mg fixed dose. MGCD0103 displays promising antitumor activity in several hematological diseases.